Lamentations - Parry, Robin A. (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 2010)
In this volume Robin Parry not only builds on traditional scholarship to interpret the book of Lamentations within its ancient context but also ventures further, exploring how the book can function as Christian Scripture. Parry provides the first systematic attempt to read Lamentations in light of the cross and resurrection. --from publisher description.
Introduction -- Lamentations 1 : no comfort -- Lamentations 2 : wrath -- Lamentations 3 : hope -- Lamentations 4 : siege and salvation -- Lamentations 5 : restore us -- Theological horizons of Lamentations.
Includes bibliographical references (p. 237-247) and indexes.
Keywords: Bible. -- Commentaries